Asymmetric adhesion of rod-shaped bacteria controls microcolony morphogenesis - Marie-Cécilia Duvernoy (Nature Portfolio, 2018)
It is unclear how cell adhesion and elongation coordinate during formation of bacterial microcolonies. Here, Duvernoy et al. monitor microcolony formation in rod-shaped bacteria, and show that patterns of surface colonization derive from the spatial distribution of adhesive factors on the cell envelope.